Academic performance and its relation with intrinsic factors in engineering students (2018)
The association between academic performance, self-regulation, psychological well-being and cognitive processes was studied in 950 students of the engineering programs of the University of Cartagena between 2014 and 2016. The academic performance was evaluated by survey from the dimensions defined by Valle-Santos et. al (2013): conceptual performance, procedural performance and global performance. Self-regulation and cognitive processes were evaluated using the instrument designed by Lindner et al (1993) called "Inventory of Self-Regulation of Learning". Psychological well-being was assessed using the psychological wellbeing scale, formulated by Ryff & Keyes (1995). For the relationship analysis, the variables were crossed and the bar diagrams and the 2x2 contingency tables were constructed applying the Chi-Square independence test. The values of 0.90, 0.89 and 0.91 for Cronbach's alpha allowed to validate the instruments: Inventory of Self-regulation of Learning, academic performance and psychological well-being, respectively. The results indicate that there is a significant degree of statistical significance (p <0.05) between academic performance with self-regulation of learning (p = 0.032), psychological well-being (p = 0.0000) and cognitive processes (p = 0.0009) at a level of 95% confidence. This means that the engineering student is an emotionally stable student, who is comfortable with the chosen career and has a high degree of abstraction, analysis and competence.